Quantitative analysis of core-shell nanoparticle catalysts by scanning transmission electron microscopy - E, H (2013)
This thesis concerns the application of aberration corrected scanning transmission electron microscopy (STEM) to the quantitative analysis of industrial Pd-Pt core-shell catalyst nanoparticles. High angle annular dark field imaging (HAADF), an incoherent imaging mode, is used to determine particle size distribution and particle morphology of various particle designs with differing amounts of Pt coverage. The limitations to imaging, discrete tomography and spectral analysis imposed by the sample’s sensitivity to the beam are also explored. Since scattered intensity in HAADF is strongly dependent on both thickness and composition, determining the three dimensional structure of a particle and its bimetallic composition in each atomic column requires further analysis. A quantitative method was developed to interpret single images, obtained from commercially available microscopes, by analysis of the cross sections of HAADF scattering from individual atomic columns. This technique uses thorough detector calibrations and full dynamical simulations in order to allow comparison between experimentally measured cross section to simulated ones and is shown to be robust to many experimental parameters. Potential difficulties in its applications are discussed. The cross section approach is tested on model materials before applying it to the identification of column compositions of core-shell nanoparticles. Energy dispersive X-ray analysis is then used to provide compositional sensitivity. The potential sources of error are discussed and steps towards optimisation of experimental parameters presented. Finally, a combination of HAADF cross section analysis and EDX spectrum imaging is used to investigate the core-shell nanoparticles and the results are correlated to findings regarding structure and catalyst activity from other techniques. The results show that analysis by cross section combined with EDX spectrum mapping shows great promise in elucidating the atom-by-atom composition of individual columns in a core-shell nanoparticle. However, there is a clear need for further investigation to solve the thickness / composition dualism.